2010
DOI: 10.1016/j.ejcts.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Results of staged total cavopulmonary connection for functionally univentricular hearts; comparison of intra-atrial lateral tunnel and extracardiac conduit

Abstract: Outcome after staged ILT- and ECC-type Fontan operations is good, with comparable freedom from late re-operations and freedom from Fontan failure at 6-year follow-up. The incidence of arrhythmias was significantly lower in the ECC group. Right ventricular morphology was identified as a risk factor for arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 23 publications
0
47
1
Order By: Relevance
“…547,548 Some cohort studies report anticoagulation or aspirin to be better than no therapy in terms of thrombotic complications, 558 although others question this fi nding. 559 The only randomized trial performed compared aspirin (5 mg/kg per day) to initial UFH followed by warfarin (target INR, 2.5; range, 2.0-3.0) as primary prophylaxis for 2 years postFontan surgery. The study found no difference in thrombosis (cumulative thrombosis rates, 19% at 2 years) or bleeding.…”
Section: Fontan Surgerymentioning
confidence: 99%
“…547,548 Some cohort studies report anticoagulation or aspirin to be better than no therapy in terms of thrombotic complications, 558 although others question this fi nding. 559 The only randomized trial performed compared aspirin (5 mg/kg per day) to initial UFH followed by warfarin (target INR, 2.5; range, 2.0-3.0) as primary prophylaxis for 2 years postFontan surgery. The study found no difference in thrombosis (cumulative thrombosis rates, 19% at 2 years) or bleeding.…”
Section: Fontan Surgerymentioning
confidence: 99%
“…6,15,16 In a direct comparison, at 6-year follow-up, the freedom from arrhythmia was 83% for the lateral tunnel Fontan and 92% for the extracardiac Fontan (Pϭ0.022). 17 Amodeo et al 18 also demonstrated a 5-year freedom from arrhythmia rate of 92% with the extracardiac Fontan. Another study looking specifically at the extracardiac Fontan reported new-onset transient supraventricular arrhythmias in 10% of patients in the early postoperative period.…”
Section: Advantage 3: Reduced Arrhythmiasmentioning
confidence: 94%
“…[51][52][53] The largest studies comparing thromboembolic events found no differences between intracardiac lateral tunnel and extracardiac Fontans, irrespective of the anticoagulant or antiplatelet treatment strategy. 25 …”
Section: Thromboembolismmentioning
confidence: 99%
“…Studies have consistently shown that postoperative Fontan pressures and transpulmonary gradients are similar with the 2 types of total cavopulmonary connections and that identical functional parameters are obtained on follow-up. 21,24,25 …”
Section: Hemodynamics and Functional Statusmentioning
confidence: 99%
See 1 more Smart Citation